Intratumoral CXCR4hi neutrophils display ferroptotic and immunosuppressive signatures in hepatoblastoma - Lu, Zhengjing; Wang, Xiaolin; Feng, Jun; Chai, Wenjia; Wang, Wei; Wang, Qixin; Yang, Shen; Yang, Wei; Su, Yan; Mou, Wenjun; Peng, Yun; Wang, Huanmin; et al. (Frontiers in Immunology, 2024)
Pediatric hepatoblastoma (HB) is the most common primary liver malignancy in infants and children. With great diversity and plasticity, tumor-infiltrating neutrophils were one of the most determining factors for poor prognosis in many malignant tumors. In this study, through bulk RNA sequencing for sorted blood and tumor-infiltrated neutrophils and comparison of neutrophils in tumor and para-tumor tissue by single-cell sequencing, we found that intratumoral neutrophils were composed of heterogenous functional populations at different development stages. Our study showed that terminally differentiated neutrophils with active ferroptosis prevailed in tumor tissue, whereas, in para-tumor, pre-fate naïve neutrophils were dominant and ferroptotic neutrophils dispersed in a broad spectrum of cell maturation. Gene profiling and in vitro T-cell coculture experiment confirmed that one of main functional intratumoral neutrophils was mainly immunosuppressive, which relied on the activation of ferroptosis. Combining the bulk RNA-seq, scRNA-seq data, and immunochemistry staining of tumor samples, CXCL12/CXCR4 chemotaxis pathway was suggested to mediate the migration of neutrophils in tumors as CXCR4 highly expressed by intratumoral neutrophils and its ligand CXCL12 expressed much higher level in tumor than that in para-tumor. Moreover, our study pinpointed that infiltrated CXCR4hi neutrophils, regardless of their differential distribution of cell maturation status in HB tumor and para-tumor regions, were the genuine perpetrators for immune suppression. Our data characterized the ferroptosis-dependent immunosuppression energized by intratumoral CXCR4 expression neutrophils and suggest a potential cell target for cancer immunotherapies.